Extraction and characterization of polysaccharides from tamarind seeds, rice mill residue, okra waste and sugarcane bagasse for its Bio-thermoplastic properties. (15th April 2018) - Chandra Mohan, C.; Harini, K.; Vajiha Aafrin, B.; Lalitha priya, U.; Maria jenita, P.; Babuskin, S.; Karthikeyan, S.; Sudarshan, K.; Renuka, V.; Sukumar, M.
Highlights: Urigam variety of tamarind seeds was found to be rich in amylose rich starch. Investigated polysaccharides were found to have high thermal stability. Crystallinity index of investigated polysaccharides were found to be in the order of SBC > TSS > RS > OMP. Okra mucilage and SBC were examined to be having linear sheets and linear bundles structures, respectively. Abstract: The aim of the present study is to extract potential thermoplastic polysaccharides from agricultural industrial wastes. Polysaccharides were extracted from renewable agro industrial wastes such as tamarind seeds [rich in starch (TSS)], okra head waste [rich in mucilage polysaccharide (OMP)], sugarcane bagasse [rich in cellulose (SBC)] and residual rice mill wastes [rich in starch and fiber (RS)]. Urigam variety of tamarind seed starch found to be an amylose rich starch. Different polysaccharides extracted from agro wastes were found to be having high thermal stability, except okra polysaccharide (comparatively low). X-ray diffraction pattern of tamarind seed starch proved its high crystallinity index. Crystallinity index of investigated polysaccharides were found to be in the order of SBC > TSS > RS > OMP. Chemical nature of extracted polysaccharides was confirmed by Fourier transform infrared spectroscopic analysis. Residual rice bran starch granules and tamarind seed starch globules were found to be having comparatively reduced particle size than sugarcane bagasse cellulose and okra mucilage. Scanning electron microscopic analysis revealed the cluster formations of RS granules and TSS globules. Residual rice bran starch found to be associated with other fibers (present in outer coat of rice). Okra mucilage and SBC were examined to be having linear sheets and linear bundles structures, respectively.